A Comprehensive Review of Eugenia Pyriformis Cambess: Reported Bioactivities and Health Effects - Dacoreggio M.V. (2023)
© 2021 Taylor & Francis.Eugenia pyriformis Cambess, commonly known as uvaia, is a native Brazilian plant. Among its benefits are the high concentration of vitamin C, carotenoids and sources of phytochemicals such as phenolic compounds. Many of these phytochemicals have been linked to the prevention and management of several chronic and degenerative diseases including cancer, cardiovascular diseases, type 2 diabetes mellitus, obesity, among other disorders. The uvaia compounds started to be isolated and characterized to provide a better understanding of the chemical mechanisms related to the biological activities of their extracts. As the identification of compounds progresses, studies investigating the potential of extract are receiving more attention. Some biological activities identified in the different uvaia compounds are antioxidants, antimicrobials, and anti-inflammatories. Previous research has pointed out that the uvaia fruit extract can be used as a potent anti-inflammatory for inhibited carrageenan-induced paw edema in rats. In this context, this review summarizes the nutritional composition of uvaia and describes the main biological activities reported for this plant, revealing some of its beneficial effects on health and highlighting how much remains to be elucidated.